2017
DOI: 10.1038/s41598-017-13341-z
|View full text |Cite
|
Sign up to set email alerts
|

Facile Solution Synthesis of Tungsten Trioxide Doped with Nanocrystalline Molybdenum Trioxide for Electrochromic Devices

Abstract: A facile, highly efficient approach to obtain molybdenum trioxide (MoO3)-doped tungsten trioxide (WO3) is reported. An annealing process was used to transform ammonium tetrathiotungstate [(NH4)2WS4] to WO3 in the presence of oxygen. Ammonium tetrathiomolybdate [(NH4)2MoS4] was used as a dopant to improve the film for use in an electrochromic (EC) cell. (NH4)2MoS4 at different concentrations (10, 20, 30, and 40 mM) was added to the (NH4)2WS4 precursor by sonication and the samples were annealed at 500 °C in air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 48 publications
5
35
0
Order By: Relevance
“…Figure 2B shows the W 4f XPS spectra of the film annealed at 250°C, and two doublets centered at approximately 36.2 and 38.3 eV can be observed. These peaks corresponded to the binding energies of W 4f 5/2 and W 4f 7/2 of W 6+ as stated in previous reports 52,53 . These peaks could be well‐fitted into two peaks and demonstrated that the tungsten ions were well oxidized to W 6+ .…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Figure 2B shows the W 4f XPS spectra of the film annealed at 250°C, and two doublets centered at approximately 36.2 and 38.3 eV can be observed. These peaks corresponded to the binding energies of W 4f 5/2 and W 4f 7/2 of W 6+ as stated in previous reports 52,53 . These peaks could be well‐fitted into two peaks and demonstrated that the tungsten ions were well oxidized to W 6+ .…”
Section: Resultssupporting
confidence: 84%
“…These peaks corresponded to the binding energies of W 4f 5/2 and W 4f 7/2 of W 6+ as stated in previous reports. 52,53 These peaks could be well-fitted into two peaks and demonstrated that the tungsten ions were well oxidized to W 6+ . As shown in Figure 2C, two O 1 second peaks located at approximately 531 and 532.7 eV were observed.…”
Section: Electrochromic Full Cell Preparationmentioning
confidence: 95%
“…Moreover, the XRD spectrum of WO 3 confirmed the monoclinic crystal structure and the corresponding peaks are similar to those reported previously. 18,19,31 On the other hand, the XRD spectrum of CdSe QD (20 s reaction time)−WO 3 confirms the changes in crystal structure of the film and the penetration of CdSe QDs into the WO 3 crystal, producing a new phase that corresponds to the orthorhombic crystal structure. 19,32,33 Figure 2d shows the FE-SEM images and surface morphology of the CdSe QD (20 s reaction time)−WO 3 and pristine WO 3 (inset).…”
Section: ■ Experimental Sectionmentioning
confidence: 78%
“…Furthermore, there have been some efforts to modify the electrochromic performance of WO 3 film for practical applications. 18,19 For example, Cai et al investigated the effect of Ti dopant for enhanced electrochromic performance of WO 3 layer. 20 An efficient performance with appropriate coloration efficiency (CE) (68 cm 2 /C at 750 nm) and rapid response time (1.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation